Ischemic Postconditioning and Nitric Oxide Administration Failed to Confer Protective Effects in a Porcine Model of Extracorporeal Cardiopulmonary Resuscitation - Psotova, Hana; Ošťádal, Petr; Mlček, Mikuláš; Kruger, Andreas; Janotka, Marek; Vondráková, Dagmar; Svoboda, Tomáš; Hrachovina, Matěj; Táborský, Luděk; Dudková, Vlasta; Strunina, Svitlana; Kittnar, Otomar; et al. (Artificial organs, 2016)
The protective effects of ischemic postconditioning (IPC) and nitric oxide (NO) administration have been demonstrated in several ischemic scenarios. However, current evidence regarding the effect of IPC and NO in extracorporeal cardiopulmonary resuscitation remains lacking. Fifteen female swine (body weight 45 kg) underwent veno-arterial extracorporeal membrane oxygenation (ECMO) implantation; cardiac arrest-ventricular fibrillation was induced by rapid ventricular pacing. After 20 min of cardiac arrest, blood flow was restored by increasing the ECMO flow rate to 4.5 L/min. The animals (five per group) were then randomly assigned to receive IPC (three cycles of 3 min ischemia and reperfusion), NO (80 ppm via oxygenator), or mild hypothermia (HT; 33.0°C). Cerebral oximetry and aortic blood pressure were monitored continuously. After 90 min of reperfusion, blood samples were drawn for the measurement of troponin I, myoglobin, creatine-phosphokinase, alanine aminotransferase, neuron-specific enolase, cystatin C, and reactive oxygen metabolite (ROM) levels. Significantly higher blood pressure and cerebral oxygen saturation values were observed in the HT group compared with the IPC and NO groups (P < 0.05). The levels of troponin I, myoglobin, creatine phosphokinase, and alanine aminotransferase were significantly lower in the HT group (P < 0.05); levels of neuron-specific enolase, cystatin C, and ROM were not significantly different. IPC and NO were comparable in all monitored parameters. The results of the present study indicate that IPC and NO administration are not superior interventions to HT for the maintenance of blood pressure, cerebral oxygenation, organ protection, and suppression of oxidative stress following extracorporeal cardiopulmonary resuscitation.
Keywords: cystatin C; Alanine Transaminase; Animals; Extracorporeal Membrane Oxygenation; mimotělní membránová oxygenace; Cystatin C; Female; alanintransaminasa; kardiopulmonální resuscitace; oxidační stres; ženské pohlaví; Troponin I; Oxidative Stress; Cardiopulmonary Resuscitation; Myoglobin; prasata; Reactive Oxygen Species; Protective Agents; krevní tlak; ischemický postconditioning; myoglobin; modely nemocí na zvířatech; Swine; Ischemic Postconditioning; Disease Models, Animal; reaktivní formy kyslíku; Creatine Kinase; oxid dusnatý; troponin I; zvířata; ochranné látky; Phosphopyruvate Hydratase; kreatinkinasa; Blood Pressure; fosfopyruváthydratasa; Nitric Oxide